Modulation of the function of the multidrug resistance-linked ATP-binding cassette transporter ABCG2 by the cancer chemopreventive agent curcumin - Chearwae W. (2014)
Curcumin (curcumin I), demethoxycurcumin (curcumin II), and bisdemethoxycurcumin (curcumin III) are the major forms of curcuminoids found in the turmeric powder, which exhibit anticancer, antioxidant, and anti-inflammatory activities. In this study, we evaluated the ability of purified curcuminoids to modulate the function of either the wild-type 482R or the mutant 482T ABCG2 transporter stably expressed in HEK293 cells and drug-selected MCF-7 FLV1000 and MCF-7 AdVp3000 cells. Curcuminoids inhibited the transport of mitoxantrone and pheophorbide a from ABCG2-expressing cells. However, both cytotoxicity and [3H]curcumin I accumulation assays showed that curcuminoids are not transported by ABCG2. Nontoxic concentration of curcumin I, II, and III sensitized the ABCG2-expressing cells to mitoxantrone, topotecan, SN-38, and doxorubicin. This reversal was not due to reduced expression because ABCG2 protein levels were unaltered by treatment with 10 μmol/L curcuminoids for 72 hours. Curcumin I, II, and III stimulated (2.4- to 3.3-fold) ABCG2-mediated ATP hydrolysis and the IC50s were in the range of 7.5 to 18 nmol/L, suggesting a high affinity of curcuminoids for ABCG2. Curcuminoids also inhibited the photolabeling of ABCG2 with [125I]iodoarylazidoprazosin and [3H]azidopine as well as the transport of these two substrates in ABCG2-expressing cells. Curcuminoids did not inhibit the binding of [α-32P]8-azidoATP to ABCG2, suggesting that they do not interact with the ATP-binding site of the transporter. Collectively, these data show that, among curcuminoids, curcumin I is the most potent modulator of ABCG2 and thus should be considered as a treatment to increase the efficacy of conventional chemotherapeutic drugs. Copyright © 2006 American Association for Cancer Research.